Metal Prices and International Market Risk in the Peruvian Stock Market - Zevallos, Mauricio (2017)
In this paper we use the conditional Value at Risk (CoVaR) and CoVaR variation (?CoVaR) proposed by Adrian and Brunnermeier (2008, 2011, 2016) to estimate the Peruvian stock market risk (through the IGBVL) conditioned on the international financial market (given that the S&P500) and conditioned on three of the main commodities exported by Peru: copper, silver and gold. Moreover, the CoVaR measures are compared with the VaR of the IGBVL to understand the differences using conditional and unconditional risk measure estimators. The results show that both CoVaR and ?CoVaR are useful indicators to measure the Peruvian stock market risk.